Pengaruh Literasi Keuangan Digital, Persepsi Kemudahan, dan Promosi Terhadap Keputusan Penggunaan E-Wallet Shopeepay Pada Mahasiswa Generasi Z di Kota Jember - Revanda Lavelia Pasa; Retno Endah Supeni; Achmad Hasan Hafidzi (MAMEN: Jurnal Manajemen, 2026)
This research examines how digital financial literacy, perceived ease of use, and promotional activities impact the decision-making of Generation Z students in Jember regarding the use of Shopeepay for cashless transactions. A quantitative approach was applied, gathering data through questionnaires from 170 respondents selected via purposive sampling. The primary data were processed using multiple linear regression analysis with SPSS version 25.The hypothesis testing results confirm that digital financial literacy (t-count = 3.870), perceived ease of use (t-count = 2.828), and promotion (t-count = 4.272) have a positive and significant effect on Shopeepay usage decisions, with promotion identified as the most influential factor. These findings suggest that while internal factors like digital financial knowledge and system convenience are important, external incentives such as promotions remain the main driver for e-wallet adoption. The novelty of this study is its focus on actual usage behavior rather than just intention, as well as the integration of literacy, ease of use, and promotion into a single research model specifically tailored to the Generation Z demographic in Jember